FENOMENA PEMEROLEHAN DAN PERKEMBANGAN BAHASA PADA ANAK USIA DINI - Ruly Adha (Jurnal Anifa: Studi Gender dan Anak, 2022)
The purposes of the article were to describe the language acquisition process of children and elaborate on the process of language development of children. This article was library research that used the descriptive qualitative method based on the data of some research or some books from some experts about language acquisition and language development. It was found that children had experienced three stages of language acquisition. In the first stage, children imitated simple sounds to show an action. In the next stage, children produced similar sounds that adults also produced. Then, children could produce and pronounce simple sentences in their native language in the last stage. Furthermore, language development consists of the process of articulation development and the process of word and sentence development.